Green Chemistry in Education: A Bibliometric Study and Research Trends (2002–2022) - Fauzia Irfani (Scientia Publica Media, 2024)
Research on green chemistry in education is always evolving. Existing studies found that incorporating green principles into undergraduate education has significant benefits. In addition to the growing interest in green chemistry among researchers, a lot of literature evaluations on green chemistry have been conducted during the past ten years. This study presents the results of a bibliometric study of 444 articles on green chemistry in education from the Scopus database in the last two decades until 2022. The literature on green chemistry has previously been mentioned in an article published in 2021 about green and sustainable chemistry education (GSCE) in mainland China. This study was conducted to see research trends on green chemistry and its implementation in education for the last two decades (2002-2022) comprehensively. Based on the analysis’ findings using VOSviewer software, the most cited documents were written by Alfonsi, Tobiszewski, and Clark. The Journal of Chemical Education is the most prolific publishing source followed by the ACS Symposium Series and Physical Sciences Reviews. The nations having the most publications are the US, Canada, and the UK. Regarding the writers who contributed the most in this field are Dicks, Eilks, and Machado. The keywords most often used are “green chemistry”, “sustainability” “laboratory instruction” and “hands-on learning/manipulatives”.